Country Partnership Framework for Bangladesh for the Period FY16-20 - World Bank Group (World Bank, Washington, DC, 2016)
Despite its challenging circumstances, Bangladesh has proven to be remarkably resilient and achieved significant human development gains. The country partnership framework (CPF) will refocus the World Bank Group’s (WBG’s) strategic direction on removing stubborn impediments to job creation and growth. The CPF will build on a well-performing portfolio, particularly in human development, identified by the systematic country diagnostic (SCD) as foundational priorities which are important prerequisites to sustained growth. Engagements from the previous strategy that promote inclusive growth - notably in health, education, and social protection, as well as in revenue mobilization, financial sector support, and the business environment - will continue. The CPF will also give greater prominence to policy reforms and make policy dialogue an integral building block in the country program. The CPF considers three selectivity criteria: (i) consistency with the government’s seventh five year plan to ensure strong country ownership; (ii) alignment with policy priorities identified in the SCD, in particular the five transformational priorities to achieve the greatest impact on poverty reduction and shared prosperity; and (iii) the WBG comparative advantage, taking into account the knowledge and financing support provided by other development partners. The activities in the CPF are structured around three focus areas consistent with the South Asia regional strategy - growth, social inclusion, and climate and environmental management.